Advances on doping strategies for triple-gate finFETs and lateral gate-all-around nanowire FETs and their impact on device performance. (May 2017) - Veloso, A.; De Keersgieter, A.; Matagne, P.; Horiguchi, N.; Collaert, N.
Abstract: This paper reviews some of the key doping strategies pursued for scaled finFET devices fabrication, addressing several of the critical integration challenges faced by this device architecture with regard to junction engineering, parasitics and series resistance control and their impact on device performance, reliability and variability. We will therefore look into the extendibility possibilities of using conventional doping techniques such as ion implantation, explore the use of novel methods to enable conformal doping of the thin body of the devices, and also evaluate junctionless vs. inversion-mode type of transistors for gate-all-around nanowire FETs, which can essentially be considered as the ultimate scaling limit of triple-gate finFETs.